Reutilization of Recycled Cellulose Diacetate From Discarded Cigarette Filters in Production of Stone Mastic Asphalt Mixtures - Liu, Huachen; Chen, Yikun; Xue, Yongjie (Frontiers in Materials, 2021)
In this paper, recycled cellulose diacetate (rCDA) derived from cigarette butts was used as fiber stabilizer to develop stone mastic asphalt (SMA) mixtures. The characterizations of rCDA were investigated by Scanning Electron Microcopy (SEM), Fourier Transform Infrared Spectrometer (FTIR) and Thermogravimetric Analyzer (TGA). Volumetric stability, temperature stability, moisture stability, and fatigue performance of SMA mixtures with rCDA were tested to discuss the pavement performance. Results showed that rCDA appeared tough surface texture with curly and corrugated structure, which facilitated to enhance the cohesion bond with asphalt binder. TG-DTG indicated the maximum weight loss (62.48%) obtained at temperature ranges from 294.1 °C to 376.0 °C due to decomposition and degradation of organic matters. While the maximum weight loss rate was obtained in the temperature range below 550 °C. When 0.4% rCDA was used in asphalt mixture, the dynamic stability was 4105 cycles/mm. The ultimate flexural strength and flexural stiffness modulus were 3722 MPa and 9.7 MPa. It indicated the temperature stability of 0.4% rCDA was superior to 0.3%PAN, while inferior to 0.3%PET. The value of tensile strength ratio and residual Marshall stability were 80.2% and 75.3% respectively. The fatigue life of 0.4% rCDA was technically like that of 0.3%PAN and 0.3%PET at lower stress levels. All results concluded that the optimum content of rCDA in asphalt mixtures was 0.4% by mass of binder.